1991
DOI: 10.1002/etc.5620100308
|View full text |Cite
|
Sign up to set email alerts
|

Decreased survival of rainbow trout exposed to no. 2 fuel oil caused by sublethal preexposure

Abstract: Rainbow trout (Oncorhynchus mykiss) were exposed for 21 d to sublethal levels of No. 2 fuel oil (2FO). The four exposure concentrations ranged from 12 to 100 mg/L 2FO dispersed in water and resulted in 0 to 12% mortality. Following this exposure period (preexposure) the ability of preexposed trout to survive exposure to acutely lethal levels of 2FO was observed. Preexposure to either 50 or 100 mg/L 2FO consistently resulted in decreased survival and a lower LC50 for a given observation period. Unfortunately, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Channel catfish exposed to contaminant effluents, showed hepatic CAT activities with dose-and time-dependent increases, but no other index of oxidative stress (malonaldehyde or methemoglobin) displayed consistent responses (Winston & Di Giulio, 1991). Moreover, Steadman et al (1991) reported a dose and time dependence of xenobiotic metabolism in rainbow trout exposed to No. 2 fuel oil.…”
Section: Resultsmentioning
confidence: 95%
“…Channel catfish exposed to contaminant effluents, showed hepatic CAT activities with dose-and time-dependent increases, but no other index of oxidative stress (malonaldehyde or methemoglobin) displayed consistent responses (Winston & Di Giulio, 1991). Moreover, Steadman et al (1991) reported a dose and time dependence of xenobiotic metabolism in rainbow trout exposed to No. 2 fuel oil.…”
Section: Resultsmentioning
confidence: 95%
“…However, long-term exposure to a pollutant does not systematically induce an increased resistance in the exposed organisms. For example, pre-exposure of yearling trout, Salvelinus fontinalis, to sublethal concentrations of lead did not induce acclimation Tang and Garside (1987) and Steadman et al (1991) even observed decreased survival of Oncorhynchus mykiss exposed to N82 fuel oil after a sublethal pre-exposure. McDonald and Wood (1993) defined the acclimation window to a pollutant as the concentration of that toxicant and the exposure time necessary to observe an increased resistance.…”
Section: Acclimation To Pollutantsmentioning
confidence: 98%
“…In contrast, previous exposure to No. 2 fuel oil decreased survival of rainbow trout [7]. Mechanisms by which tolerance of a population can change include physiological acclimation and genetic selection.…”
Section: Introductionmentioning
confidence: 99%